3
$\begingroup$

I have to calculate $\sum\limits_{n=1}^{\infty} \frac{a\cos(nx)}{a^2+n^2}$ for $x\in(0,2\pi)$.

I have used the function $f(x)=e^{ax}$ and I have calculated the Fourier coefficients which are: $$a_0=\dfrac 1{2a} \dfrac {e^{2\pi a}-1}{\pi}$$ $$a_n=\dfrac {e^{2\pi a}-1}{\pi} \dfrac{a}{a^2+n^2}$$ $$b_n=\dfrac {e^{2\pi a}-1}{\pi} \dfrac{-n}{a^2+n^2}$$

In the end, when it is written as Fourier series: $$e^{ax}=\frac{e^{2\pi a}-1}{\pi}\left(\frac{1}{2a}+\sum^\infty_{n=1}\frac{a\cos(nx)-n\sin(nx)}{a^2+n^2}\right),\text{ for }x\in(0,2\pi).$$

My question is how can I use all these facts to calculate $\sum\limits_{n=1}^{\infty} \frac{a\cos(nx)}{a^2+n^2}$?

$\endgroup$
  • $\begingroup$ As an aside, for $x=2k\pi$, we have $\displaystyle\sum_{n=-\infty}^{\infty} \frac{a}{a^2+n^2} ~=~ \pi\coth(a\pi)$, and for $x=(2k+1)\pi$, we have $\displaystyle\sum_{n=-\infty}^{\infty} \frac{a(-1)^n}{a^2+n^2} ~=~ \pi~\text{csch}(a\pi)$. This can be easily shown by differentiating the natural logarithm of Euler's infinite product expansion for the sine and cosine functions. $\endgroup$ – Lucian Oct 14 '15 at 20:56
6
$\begingroup$

Or equivallently, we can choose : $f(x)=\cosh ax$, then

$$f(x)=\frac{a_0}{2}+\sum_{n=1}^\infty a_n\cos nx + b_n \sin nx$$

where, since $f(x)$ is symmetric, $b_n =0$ and also

$$a_n=\frac{2}{\pi}\int_0^\pi\cosh ax \cos nx \;\mathrm{d}x=\frac{2a}{\pi}\frac{\sinh\pi a}{a^2+n^2}\,\cos{\pi n}$$

hence

$$\cosh ax= \frac{2}{\pi}\frac{\sinh\pi a}{2a}+a\sinh\pi a\sum_{n=1}^\infty\frac{2}{\pi}\frac{\cos{\pi n}\cos n x}{a^2+n^2}$$

For $x=\pi-y$ we get :

$$\cosh a(\pi-y)= \frac{2}{\pi}\frac{\sinh\pi a}{2a}+a\sinh\pi a\sum_{n=1}^\infty\frac{2}{\pi}\frac{\cos n y}{a^2+n^2}$$

Rearanging and renaming $y \rightarrow x$ :

$$\sum_{n=1}^\infty\frac{a \cos n x}{a^2+n^2}= \frac{\pi\cosh a(\pi-x)}{2\sinh \pi a}-\frac{1}{2a} \quad\quad ;\text{for}\quad x\in [0,2\pi]$$

Addendum :

$$\sum_{n=-\infty}^\infty\frac{a \cos n x}{a^2+n^2}= \frac{\pi\cosh a(\pi-x)}{\sinh \pi a}\quad\quad ;\text{for}\quad x\in [0,2\pi]$$

Substituing $x=0$

$$\sum_{n=-\infty}^\infty\frac{a}{a^2+n^2}= \pi\coth \pi a$$

and $x=\pi$

$$\sum_{n=-\infty}^\infty\frac{a(-1)^n}{a^2+n^2}= \pi\operatorname{csch} \pi a$$

which coincides with @Lucian's commentary.

$\endgroup$
  • $\begingroup$ - I am sorry for calculation errors, they will be corrected $\endgroup$ – Machinato Jul 20 '16 at 22:05
  • $\begingroup$ Alternately, we could have tried solving $~\dfrac{S''(x)}a-aS(x)=\dfrac12,~$ where the last term stems from the value of the infinite series symbolically written as $~\displaystyle\sum_{n=1}^\infty\cos(nx).$ $\endgroup$ – Lucian Jul 24 '16 at 14:04
1
$\begingroup$

Your function $f$ is the periodic function of period $2\pi$, that is equal to $\exp(ax)$ for $x\in (0,2\pi)$. Hence for $x\in(0, 2\pi)$, you have $f(-x)=f(2\pi-x)=\exp(a(2\pi-x))$. You can calculate this by your Fourier expansion; and now add the expressions for $f(x)$ and $f(-x)$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.